2021
DOI: 10.1038/s41598-021-95297-9
|View full text |Cite
|
Sign up to set email alerts
|

Suitable binder for Li-ion battery anode produced from rice husk

Abstract: Rice husk (RH) is a globally abundant and sustainable bioresource composed of lignocellulose and inorganic components, the majority of which consist of silicon oxides (approximately 20% w/w in dried RH). In this work, a RH-derived C/SiOx composite (RHC) was prepared by carbonization at 1000 °C for use in Li-ion battery anodes. To find a suitable binder for RHC, the RHC-based electrodes were fabricated using two different contemporary aqueous binders: polyacrylic acid (PAA) and a combination of carboxymethyl ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…The primary role of the polymeric binder is to create chemo-mechanical stability at two scales: (1) the particle scale to prevent pulverization by creating an adhesive layer at the particle surface and (2) the electrode wide mesoscale to provide structural stability between the different composite electrode components during cycling. , Therefore, a binder should have specific chemical functionality to adhere to the active material particle surface and have functionalities that provide for mechanical characteristics that can accommodate volume expansions/contractions. Both properties are integral to achieving stable electrochemical performance in a composite electrode.…”
Section: Introductionmentioning
confidence: 99%
“…The primary role of the polymeric binder is to create chemo-mechanical stability at two scales: (1) the particle scale to prevent pulverization by creating an adhesive layer at the particle surface and (2) the electrode wide mesoscale to provide structural stability between the different composite electrode components during cycling. , Therefore, a binder should have specific chemical functionality to adhere to the active material particle surface and have functionalities that provide for mechanical characteristics that can accommodate volume expansions/contractions. Both properties are integral to achieving stable electrochemical performance in a composite electrode.…”
Section: Introductionmentioning
confidence: 99%
“…The number of oxygen atoms ( x ) in SiO x in the RH carbonized at 1000 °C was found to be close to 2 17 . Under this assumption, the SiO x in C/SiO x AMs can react with Li ions according to the following chemical formulae [Eqs.…”
Section: Resultsmentioning
confidence: 88%
“…Ju et al stated that RH-derived C/SiO x exhibits a large irreversible capacity of 46.7% Coulombic efficiency (CE) at the initial Li-ion insertion and extraction 22 . Kumagai et al also reported ~ 53% CE at the initial Li-ion uptake and release 17 . The large irreversible capacity of RH-derived C/SiO x has been demonstrated elsewhere 15 , 20 – 23 .…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations